Mechanism of Support Optimization and Confined Blasting of Thick and Hard Rock with a Wedge-Structure Immediate Roof: A Case Study. (21st July 2021) - Zhao, Tong; Gong, Peilin; Yetilmezsoy, Kaan; Bahramian, Majid; Liu, Changyou; Gong, Xiaofei
Abstract : Based on the occurrence conditions of a thick and hard main roof and wedge-structure immediate roof in the Zhuxianzhuang Coal Mine, the fracture characteristics and instability migration law of a thick and hard roof (THR) were examined via physical simulations. Mining zones were divided with respect to the strata behaviors and roof control difficulty levels, and the principles and methods of zonal control under THR were put forward. This study proposed a coordinated control strategy of using confined blasting in water-filled deep holes, and reasonable support optimization, which could effectively reduce the roof fracture size, increases the supporting intensity and eliminate roof-control disasters. The length of confined blasting blocks and supporting intensity were calculated using a mechanical model for roof control in the strong strata behavior zone and less-strong strata behavior zone. These key parameters were determined as 20–25 m and 1.15–1.28 MPa, respectively, and the mining strategy was successfully applied in working face 880, performing high security and reasonable economical efficiency.